2014
DOI: 10.1136/annrheumdis-2014-205585
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between radiographic joint space narrowing, sonographic cartilage thickness and anatomy in rheumatoid arthritis and control joints

Abstract: Sonographic cartilage assessment in MCPs is closely related to anatomical cartilage thickness. Both JSW and JSN by radiography represent cartilage thickness in the MCP joints of patients with RA quite well. Thus, US is a valid tool for measuring MCT if radiographs are not available or in case of joint malalignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…One of the most intriguing findings of our study was the prominent cartilage damage in patients with HH-A, particularly in the MCP joints. In RA, a reduction in cartilage thickness has been shown to predict disability after 1–2 years, while it did not correlate with health assessment questionnaire (HAQ) scores at baseline [ 29 , 30 ]. We also observed that neither ultrasound scores nor x-ray findings were associated with pain, global assessment and function; however, ultrasound abnormalities correlated strongly with x-ray-verified structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most intriguing findings of our study was the prominent cartilage damage in patients with HH-A, particularly in the MCP joints. In RA, a reduction in cartilage thickness has been shown to predict disability after 1–2 years, while it did not correlate with health assessment questionnaire (HAQ) scores at baseline [ 29 , 30 ]. We also observed that neither ultrasound scores nor x-ray findings were associated with pain, global assessment and function; however, ultrasound abnormalities correlated strongly with x-ray-verified structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 17 patients (65%) who completed the 10-year MRI, cartilage thickness appeared to be preserved. Measurements of cartilage thickness represent radiographic joints space width or joint space narrowing [3,12], which is considered the reference standard for assessment of progression of hip OA. Jacobsen et al [10] reported that joint space width less than 2 mm is associated with patient-reported pain in or around the hip, which is in line with the acceptable pain scores of the 17 patients who did not experience thinning of the cartilage during the 10-year period after PAO.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormally hypoechoic (loss of normal fibrillar architecture) and/or thickened tendon or ligament at its bony attachment (may occasionally contain hyperechoic foci consistent with calcification), seen in 2 perpendicular planes that may exhibit Doppler signal and/or bony changes including enthesophytes, erosions, or irregularity et al 26 conducted a study aimed at validating US for measuring cartilage thickness at the metacarpophalangeal (MCP) joint level comparing the findings with anatomical measurement using cadaver specimens; moreover, a correlation with radiography in the assessment of joint space narrowing was performed. Both good agreement between US and cartilage thickness and positive correlation with joint space narrowing (P < 0.001) were found.…”
Section: Us Finding Definitionmentioning
confidence: 98%
“…These results encourage consideration of the US as a valid tool for measuring cartilage thickness in RA patients. 26 Ultrasound may be considered the "criterion standard" imaging tool for the assessment of tendons. 27,28 Its spectrum of application is wide and includes the detection of tenosynovitis and anatomical damage represented by the loss of the normal fibrillar echotexture and loss of definition of the tendon margins (Fig.…”
Section: Us Finding Definitionmentioning
confidence: 99%